Towards a full body narrative: a communicational approach to techno-interactions in virtual reality - Zilles Borba, Eduardo (Lumina, 2020)
The essay approaches the sociocultural and technological issues linked to the communicational process that exists in the user’s relationship with immersive digital environments, specifically: Virtual Reality (VR). A critical look at VR as a communication interface is launched, precisely because it indicates assumptions of enhancing the creation of meanings on media surfaces by leveraging multisensory stimuli that cause the immersion of individual’s body in a 360° framed experience. To instigate the problematization about transformations resulting from these techno-experience, empirical explorations are conducted to Brazilian immersive environments. In addition, data are qualitatively analyzed based on Kerckhove, Gumbrecht and Flusser and others ideas to illuminate the debate of technical-images, digital narratives and appropriations on technological devices, media languages and coding in the digital age.